(untitled) (Tribhuvan University Law Journal, 2025)
Rationale of this research is to educate its stakeholders regarding concept, legal provisions and practices of enforcement of contract in relation to ownership transfer of immovable property especially court order of specific performance since uncertainty or penumbra prevails in this area of law. In addition researcher recommends various circumstances to the judges for granting order of specific performance in this area. This research work has applied doctrinal research methods. Primary data are collected from the laws and decisions and secondary data are collected from the published research works, books, journals, articles, electronic media, etc. Findings of the research is that, court order granting specific performance on the basis of agreement to sale contract for ownership transfer of immovable property is also meant an order given to the Land Revenue Office for the registration of a sales deed or sales contract to transfer ownership right on immovable property from seller to the buyer. Court can grant an order of specific performance on contract of ownership transfer of immovable property considering various recommended circumstances. Such recommendations are, court must consider various circumstances in addition to the legal requirements such as; contract must fulfill requirements as prescribed in the law or registration requirement; said order shall be granted only in favor of the buyer; buying immovable property must not be for money making or real estate motive; order is granted only to the residential purchaser; immovable property must be unique or at least an acceptable substitute is not readily available in the market; said order is an equitable and discretionary remedy or prerogative power of the court; prospective buyer at first must attempt to perform the contract by depositing the said amount in the court (Nepalese court practice) and etc. Conclusion of this research work is, ‘Order of specific performance as an enforcement of contract shall be granted if agreement to sale contract for ownership transfer of immovable property is registered, prospective buyer proved that compensation is not adequate, and all the conditions as prescribed in law for the order of specific performance has been satisfied.’